Research joint ventures and firm level performance: Special issue on science and technology policies towards research joint ventures - Luigi Benfratello; Alessandro Sembenelli (Fondazione Eni Enrico Mattei (FEEM), 2000)
In this paper we test whether participation in EU sponsored Research Joint Ventures (RJVs) has a positive impact on participating firms' performance. We apply our statistical methodology to RJVs sponsored under two different programmes: EUREKA and (3rd and 4th) Programme Frameworks for Science and Technology (PFST). Overall results show a positive association between participation, labour and total factor productivity, and price cost margin only in the case of EUREKA. On the contrary, firms participating FPST RJVs do not show any clear pattern.
Keywords: O31; O38; 330; Research Joint Ventures; European Union; economic performance; Forschungskooperation; Unternehmenserfolg; Europäische Forschungs- und Technologiepolitik; EU-Staaten